Absence of neonatal intensive care units in secondary medical care zones is an independent risk factor of high perinatal mortality in Japan. Issue 10 (16th June 2016) - Matsumoto, Yoko; Nakai, Akihito; Nishijima, Yasuhiro; Kishita, Eisaku; Hakuno, Haruhiko; Sakoi, Masami; Kusuda, Satoshi; Unno, Nobuya; Tamura, Masanori; Fujii, Tomoyuki
Abstract: Aim: National medical projects are carried out according to medical care plans directed by the Medical Care Act of Japan. In order to improve Japanese perinatal medical care, it is necessary to determine the factors that might influence perinatal outcome. Methods: Statistical data of births and perinatal deaths were obtained for all municipalities in Japan from 2008 to 2012 from the Portal Site of Official Statistics of Japan (e‐Stat). The perinatal mortality of all 349 Japanese secondary medical care zones was calculated. The number of neonatal intensive care units (NICUs), maternal‐fetal intensive care units (MFICUs), pediatricians and obstetricians in 2011 were also obtained from e‐Stat. Nine secondary medical care zones in two prefectures, Fukushima (7) and Miyagi (2) were excluded to eliminate the influence of the 2011 Great East Japan Earthquake. Results: The 340 secondary medical care zones were divided into three groups according to population size and density: metropolis, provincial city, and depopulation. The number of secondary medical care zones in each group were 52, 168, and 120, respectively. The secondary medical care zones in the depopulation group had fewer pediatricians and significantly fewer NICUs and MFICUs than the metropolis group, but there was no significant difference in perinatal mortality. The only independent risk factor for high perinatal mortality, determined by multivariable analysis, was the absence of an NICU ( P = 0.011). Conclusions: To consider directions in perinatal medical care, planned arrangement and appropriate access to NICUs is indispensable.